Soil microbial community assembly precedes vegetation development after drastic techniques to mitigate effects of nitrogen deposition - van der Bij, A.U.; Pawlett, M.; Harris, J.A.; Ritz, Karl; van Diggelen, R. (0006-3207, 2016)
Oligotrophic semi-natural systems are threatened by high levels of nitrogen deposition. To mitigate these effects, drastic techniques such as sod-cutting and topsoil removal are applied to reduce nitrogen loads in existing systems and expand their area on former agricultural fields. We assessed the effects of these techniques along with the influence of previous land-use, isolation and vegetation development on subsequent microbial community assembly in restored agricultural areas. Microbial community phenotypic structure was measured using PLFA-analysis, along with soil chemistry and vegetation development. Differences in soil nitrogen pools due to restoration techniques were the most differentiating factor for both microbial community assembly and vegetation development. Only after topsoil removal was resemblance of both below- and above-ground communities to well-developed heathlands increased within 10–15 years. After sod-cutting both microbial community and vegetation composition remained more similar to agricultural sites. The relative contribution of agricultural sites and heathlands in the direct vicinity had more pronounced effects on local microbial community composition than current land-use in all study sites including agricultural areas and heathlands. Vegetation development was apparently of minor importance for microbial community assembly, since characteristic belowground assembly preceded that of aboveground development in both restoration contexts.